Reverie mirrors in the distance - Orosa, Marily Ysip; Gimenez, Zeny Amistoso; Monroy, Annelle Militante (Manila Studio 5 Designs, Inc., 2014)
Collection of stories from alumni of St. Theresa's College.
Yin and yang / Melinda Tolosa Alcober Solo flight Edna Alikpala Somewhere between rhymes and riddles Elenita Belgica Test of faith Mariza Cuevas Ceñido Rose of Pasadena Ching Ong de la Cruz A great adventure Evelyn Doliente de la Cruz Staying the course Vicki Hernandez de Jesus Impo and Lola Lydia Balatbat Echauz Father knows best Tina Joaquin Erum Tapestry Arleen Indiongco Estrella The vow zeny Amistoso Gimenez A walk in the park Eloisa Garcia Guevara Rhythm in blue Emmy Lagniton Hayward Full circle Alma Cuevas Horrilleno The long and winding road Agnes Alvarez Kalisher I am content Cynthia de la Fuente Lota Driven Teresita Geraldez Mascardo Somewhere in time Nanette Katigbak Medina Diamonds in my mind Annelle Militante Monroy Fly away Marily Ysip Orosa The governor's daughter Nancy Sison Roxas Ride of my life Marieke Chan Samonte Under the avocado tree Bobbi Santos-Viola Yesterday once more Carmen Chua Say The good news Melissa Ochangco Simpao In his time Marile Cepeda Sison Dance of life Ditsy Casimiro Sumpaico Serendipity Marleen Imperial Villarreal Happily ever after Cynthia Dancel Villasis In a secular world Natividad Madrid Yabes Search for my authentic self Sita Castro Yan
In English.
Keywords: Philippine essays (English) -- Women authors; Short stories, Philippine (English)